Diagnostic Value of Combined Acute Levodopa Challenge and Olfactory Testing to Predict Parkinson's Disease - Terroba Chambi, Cinthia (Mov Disord Clin Pract, 2017)
BACKGROUND: The diagnosis of Parkinson's disease (PD) can be challenging early in the disease course, when motor features are subtle. The objective of this study was to explore the diagnostic value of combining acute levodopa challenge and olfactory testing to predict PD. METHODS: Data from 210 patients with a recent onset of parkinsonism who had at least 2 years of follow‐up and underwent acute levodopa challenge for the clinical prediction of long‐term dopaminergic response and had olfactory testing with Sniffin’ Sticks Test were evaluated. Single and combined diagnostic measures were analyzed. RESULTS: After 2 years of follow‐up, a PD diagnosis was confirmed in 157 patients who fulfilled United Kingdom Parkinson's Disease Society Brain Bank criteria and was ruled out in 53. Sensitivity and specificity of acute levodopa challenge to predict PD diagnosis were 0.71 and 0.94, respectively. Sensitivity and specificity of olfactory tests were calculated according to the total olfactory score for hyposmia (0.61 and 0.77 respectively), the hyposmia identification subscore (0.63 and 0.74, respectively), and the anosmia score (0.40 and 0.85, respectively). The best combination identified was response to acute levodopa challenge together with hyposmia according to the total olfactory score (sensitivity, 0.90; specificity, 0.74; positive predictive value, 0.91; negative predictive value, 0.72; accuracy, 0.86). CONCLUSION: The combination of response to acute levodopa challenge with hyposmia according to the total olfactory score improved sensitivity for the early diagnosis of PD.